Dual Realities of Resources Challenges and Market Opportunities in Small Scale Enterprises of Namakkal District - K. Balakrishnan; Dr. T. Asothai (IJRDO - Journal of Business Management, 2025)
This study investigates the dual realities of challenges and opportunities experienced by small-scale enterprises (SSEs) in Namakkal district, Tamil Nadu. Anchored in an empirical and quantitative framework, the research surveyed 130 enterprises selected through stratified random sampling across five clusters: agro and poultry, textiles, food processing, transport-related services, and other small-scale manufacturing. Primary data were collected using a structured interview schedule and analysed through descriptive statistics, Chi-square tests, ANOVA, and multiple regression modelling. The findings reveal that financial constraints represent the most significant barrier to enterprise performance with regression results showing a strong negative relationship between finance-related challenges and outcomes. The study contributes an integrative framework positioning performance as the outcome of both constraints and opportunities. Entrepreneurial strategies highlight the importance of digital adoption, managerial strengthening, and diversification for enhancing competitiveness.